Nelson's way - Jones, Stephanie (London Nicholas Brealey, 2005)
This is a one-of-a-kind look at Nelson and his leadership skills Vice Admiral Horatio Lord Nelson has been widely admired as a celebrated and effective leader. His dynamic approach to leadership and management has now been translated into a timeless, practical and contemporary insight for today's managers. Nelson's Way will bring 'The Nelson Touch' of luck, inspiration and leadership to everyone. Explaining how Nelson embodies the characteristics of the most successful of leaders, from bravery to determination, inspiration to luck and simplicity to unconventionality. Jones and Gosling explore and examine the self-made legend set against the backdrop of the high-seas, personal sacrifice, debilitating injuries and glorious conquests. With chapters including: Making Heroes, The Band of Brothers and Creating (and Sustaining) a Legend, Nelson's Way incorporates the latest research and joins a series of ground-breaking studies applying historical biography to business to create the most comprehensive insight into Nelson, his heroic exploits and legendary leadership skills.
Includes bibliographical references and index.
Keywords: Nelson, Horatio Nelson, Viscount, 1758-1805 -- Military leadership; Leadership